TKI-Resistant Renal Cancer Secretes Low-Level Exosomal miR-549a to Induce Vascular Permeability and Angiogenesis to Promote Tumor Metastasis - Xuan, Zuodong; Chen, Chen; Tang, Wenbin; Ye, Shaopei; Zheng, Jianzhong; Zhao, Yue; Shi, Zhiyuan; Zhang, Lei; Sun, Huimin; Shao, Chen (Frontiers in Cell and Developmental Biology, 2021)
Tyrosine kinase inhibitors (TKI)-resistant renal cancer is highly susceptible to metastasis, and enhanced vascular permeability promotes the process of metastasis. To evaluate the effect of cancer-derived exosomes on vascular endothelial cells and clarify the mechanism of metastasis in TKI-resistant renal cancer, we studied the crosstalk between clear cell renal cell carcinoma (ccRCC) cells and human umbilical vein endothelial cells (HUVECs). Exosomes from ccRCC cells enhanced the expression of vascular permeability-related proteins. Compared with sensitive strains, exosomes from resistant strains significantly enhanced vascular endothelial permeability, induced tumor angiogenesis and enhanced tumor lung metastasis in nude mice. The expression of miR-549a is lower in TKI-resistant cells and exosomes, which enhanced the expression of HIF1α in endothelial cells. In addition, TKI-resistant RCC cells reduced nuclear output of pre-miR-549a via the VEGFR2-ERK-XPO5 pathway, and reduced enrichment of mature miR-549a in cytoplasm, which in turn promoted HIF1α expression in RCC, leading to increased VEGF secretion and further activated VEGFR2 to form a feedback effect. MiR-549a played an important role in the metastasis of renal cancer and might serve as a blood biomarker for ccRCC metastasis and even had the potential of becoming a new drug to inhibit TKI-resistance.